CO2 and H2O adsorption-desorption cycles for multifunctional Ni-Fe based catalyst in the production of Synthetic Natural Gas - Mercader Plou, Víctor Daniel; Sanz-Martínez, Andrés; Durán, Paul; Francés, Eva; Herguido, Javier; Peña, José Ángel (Jornada de Jóvenes Investigadores del I3A, 2022)
A study of the affinity of lab-made multifunctional catalysts to adsorb-desorb CO2, H2 and H2O has been carried out by thermogravimetry in the Hydrogen Technologies Laboratory of I3A. Higher CO2 affinities were showed by multifunctional catalyst in comparison with the nonfunctionalized FeNi catalyst.